Cracking behavior of donax grandis natural fibre reinforced polymer composite - Eng, K.S (University Malaysia Sarawak, (UNIMAS), 2005)
The awareness of using the polymer synthetic fibre in composite material has been an issue of environmental pollution. In the selection of material in low strength engineering application, the natural fibre is an alternative to replace the synthetic fibre in certain extent especially in automobile industry. In this research the mechanical properties of natural fibre, Donax Grandix mixed unsaturated polyester is used to fabricate the specimen with fibre volume fraction of 0.6 and 0.4